2022
DOI: 10.3390/fermentation8030112
|View full text |Cite
|
Sign up to set email alerts
|

Production of a Yogurt Drink Enriched with Golden Berry (Physalispubescens L.) Juice and Its Therapeutic Effect on Hepatitis in Rats

Abstract: Fermented dairy products have been associated with multiple health benefits. The present study aimed to produce a functional yogurt drink fortified with golden berry juice and assess its therapeutic effect on hepatitis rats. Thirty male albino rats were randomly divided into two major groups. The first group included the control (-) animals (six rats) and was fed a standard diet, whereas the second group included 24 rats that were fed a standard diet and injected with carbon tetrachloride (CCl4) for 2 weeks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…fruit extracts have shown potent α-glucosidase inhibitory activity due to the presence of a considerable amount of casuarictin that can work well to inhibit α-glucosidase (Xu et al 2023). Therefore, these foods or their ingredients can be incorporated with several food products to enhance their nutritional value, quality attributes such as texture, color, flavor, taste, shelflife, and other, and health properties such as antioxidant, antidiabetic, antiobesity, antimicrobial, anticancer, and other (Buchilina 2021;Chen et al 2019a;Huang et al 2022;Rashwan et al 2020;Rashwan et al 2022;Rashwan et al 2021;Shahein et al 2022). Recently, many studies reported that yogurt is considered one of the most important food products that can be compatible with other food ingredients.…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…fruit extracts have shown potent α-glucosidase inhibitory activity due to the presence of a considerable amount of casuarictin that can work well to inhibit α-glucosidase (Xu et al 2023). Therefore, these foods or their ingredients can be incorporated with several food products to enhance their nutritional value, quality attributes such as texture, color, flavor, taste, shelflife, and other, and health properties such as antioxidant, antidiabetic, antiobesity, antimicrobial, anticancer, and other (Buchilina 2021;Chen et al 2019a;Huang et al 2022;Rashwan et al 2020;Rashwan et al 2022;Rashwan et al 2021;Shahein et al 2022). Recently, many studies reported that yogurt is considered one of the most important food products that can be compatible with other food ingredients.…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
“…Recently, many studies reported that yogurt is considered one of the most important food products that can be compatible with other food ingredients. Besides, the addition of natural functional ingredients to yogurt has significantly gained consumers' acceptance because of the health benefits of both yogurt and natural functional ingredients (Table 1) (Ahmad et al 2023;Basiri et al 2022;Guadarrama-Flores et al 2022;Huang et al 2022;Rashwan et al 2022;Shahein et al 2022;Tami et al 2022;Tang et al 2022).…”
Section: Natural Functional Ingredientsmentioning
confidence: 99%
“…Shahein et al. (2022) made a functional yoghurt drink enriched with berry juice, which improved the polyphenol content and sensory scores of the drink, which also showed hepatoprotective effects in rats with hepatitis. Ozturkoglu‐Budak et al.…”
Section: Addition Of Dietary Supplements—diversification Of Functions...mentioning
confidence: 99%
“…bulgaricus (Farag et al ., 2021). It is widely consumed worldwide and offers a range of health benefits due to its unique properties (Fazilah et al ., 2018; Matos et al ., 2021; Shahein et al ., 2022). Yoghurt is renowned for its pleasant flavour and texture (Vénica et al ., 2019) and can be enjoyed in various forms such as meal substitutes, beverages, desserts, snacks, and protein‐rich drinks, among others.…”
Section: Introductionmentioning
confidence: 99%